Behaviour and performance of anthocyannins Brassica oleracea and their co-pigments in food hydrocolloids / Herda Farhana Sukhirman - Herda Farhana , Sukhirman (2017)
Anthocyannins are pigments with attractive colours, ranging from red at low pH, to blue and green at high pH. Anthocyannins can be found in a number of natural sources, including strawberries, sweet potatoes, yams, grapes, and red cabbages. In this work, the effects of ultraviolet (UV) radiation on the degradation of anthocyannins from red cabbages, incorporated in food hydrocolloids will be investigated, in terms of anthocyannin colour stability and change in concentration. To study short term and long term effects of UV exposure to anthocyannins in food application, three types of UV radiation, namely UV-A, UV-B, and UV-C were used. The UV effects were demonstrated by increasing the frequency of the radiation. In the first part of the work, the anthocyannins were extracted from red cabbages, and purified using double chromatographies, namely ion exchange chromatography and size exclusion chromatography. The later extracts the pigment better than the former, as distinct fraction colours were observed during the process. The anthocyannin extract was freeze-dried and stored at - 20°C until used in food hydrocolloids, namely agar, carrageenan and gelatine for the UV study. Liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) was also performed on the purified anthocyannins, and the results confirmed the presence of cyanidins in the sample. pH differential method was done to calculate the total monomeric content of anthocyannins in the red cabbage sample, prior to UV exposure. The pure anthocyannin was applied in food hydrocolloids, namely agar, carrageenan and gelatine for the UV study. In the second part of the work, colorimetric study i.e. CIELAB and chemometric study i.e. FT-IR spectroscopy were performed to evaluate anthocyannin colour stability, and change in anthocyannin concentration, respectively. The anthocyannin samples were mixed with copigments, namely cinnamic acid, ferulic acid, and gallic acid, to study the performance of anthocyannins with the copigments. In the colorimetric study, all hydrocolloid samples containing anthocyannin became fader throughout 35 days of storage under exposure to UV radiations as the radiations were destructive, and cross-linking of hydrocolloids was enhanced under UV exposure, which caused changes in hue and lightness. The effects became more pronounced from UV-A to UV-B and UV-C, as the frequency of radiation was increased. However, samples containing anthocyannin-copigment complexes were duller than samples without copigment, as the water contained in the hydrocolloids suppressed copigmentation. In the FT-IR spectroscopy, concentration of anthocyannins was shown to generally decrease during the 35 days of storage under exposure to UV radiations and the effects became more pronounced from UV-A to UV-B and UV-C, due to destructive effects of UV radiations. In conclusion, UV-C has the greatest effect on the degradation of anthocyannin, followed by UV-B and UV-A, in a given period of time. This means that when anthocyannins are incorporated in food, the degradation becomes increasingly faster from UV-A to UV-B and UV-C. In the future, it may be possible to manipulate the chemical bonds and functional groups of anthocyannin to generate new colours, which can then be applied for industrial use, such as in textile dyeing.